Profile of anaerobic bacteriology of middle ear aspirates in a developing country: Does immunocompromise play a role? (2014)
Objectives: The study intends to report the profiles of anaerobic bacteria isolated and attempts to evaluate the impact of immunocompromised status of patients on the disease. Study design: A cross-sectional prospective study. Setting: ENT clinic, University of Ilorin Teaching Hospital, Nigeria; a 450-bed tertiary health facility. Subjects: 104 consecutive consenting participants with clinical evidence of CSOM >12 weeks. Methods: A hospital-based study conducted over a seven (7) month period. The middle ear aspirate was obtained with the aid of a micropipette and sent immediately for Microscopy, Culture and Sensitivity of both anaerobic and aerobic bacterial isolates. Results: A total of 11 patients with chronically discharging ears, of the 104 studied had anaerobic bacteria cultured from their middle ear aspirates. Age ranged from 4 to 50 years with a male:female ratio of 1:1.8. A total of 32 isolates (11 anaerobic and 21 aerobic) were recovered. All anaerobic organisms were mixed and included both Peptostreptococcus and Bacteroides. Metronidazole had 100% sensitivity to gram negative and 62.5% to gram positive anaerobic organisms tested. Five (5) patients had immunocompromised states of 11 patients with anaerobic bacteria isolated in middle ear aspirates (group I), while 13 immunocompromised patients of the remaining 93 patients with no anaerobic bacteria isolated (group II). The proportion of anaerobic isolates in group I is higher (p < 0.05) than in group II. Conclusion: Immunocompromised state and age appear to play key role in presence of the anaerobic organisms recovered from the middle ear of the patients studied.